Giordano Brunos konzeption des schönen in "De gli eroici furori" (Estudios Humanísticos. Filología, 1995)
The main of this paper is to examine Giordano Bruno's conception of beauty his book De gli Eroici Furori. Firstly, I place Bruno's conception of beauty in the frame of his theory of knowledge, whose central problem is how we can know the divinity. Next, I connect Bruno's analysis of beauty with 'the problem of form and harmony, which is traced back to the classical problemof unity in variety. On this basis I examine the question about how we can know the beauty in the world. The knowledge of beauty requires that the beauty in the world is given a spiritual form, the unity of the idea, i.e. it requires the acknowledgement of its divine origin.